Inhibin/activin expression in human and rodent liver: subunits α and βB as new players in human hepatocellular carcinoma? - Frost, K (Nature Publishing Group, 2011)
BACKGROUND: Activins and inhibins belong to the TGFβ-superfamily, which controls cell proliferation and differentiation in many organs. Activin A, the dimer of inhibin βA subunit, acts strongly anti-proliferative in hepatocytes. Little is known on the other activin/inhibin subunits in human liver and hepatocellular carcinoma (HCC). METHODS: We studied the expression of the complete inhibin family α, βA, βB, βC, βE in normal liver, tumour-adjacent and HCC tissue, 12 additional organs and rodent liver. A total of 16 HCC and 10 disease-free livers were analysed. Expression of inhibin subunits was determined by qRT–PCR, normalised to RNA input and by geNorm algorithm, and confirmed by immunohistochemistry. RESULTS: Remarkably, βA expression was not decreased in HCC. Similarly, βC and βE exhibited no major changes. In contrast, inhibin α, barely detectable in normal liver, was strongly increased in tumour-adjacent liver and dramatically enhanced in HCC. βB was strongly enhanced in some HCC. At variance with human liver, rodent liver showed higher inhibin α and βC expression, but βA was somewhat, and βB dramatically lower. CONCLUSIONS: Upregulation of inhibin α – and possibly of βB – may shield HCC cells from anti-proliferative effects of activin A. Dramatic variations between humans and rodents may reflect different functions of some inhibins/activins.